TOOLS OF THINKING PREFERRED BY MANUFACTURING STUDENT OF UTEM - Ahmat, Norunnajjah (Journal of Human Capital Development (JHCD), 2021)
ABSTRACT This article meant to investigate the choices of thinking tools among Manufacturing Student of UTeM. The manufacturing student involved was one BMFG from the Faculty of Manufacturing. There are 10 groups in the class. Each group were given an assignment to write one out of seven thinking tools taught in the class. The thinking tools are Brainstorming, Mind Map, SCAMPER, 6 Thinking Hat, SWOT, CPSP and Design Thinking. The finding is that these manufacturing students preferred three thinking tools which are mind map, SCAMPER and 6 Thinking Hats; wherein mind map is the major choice. It is remarkable that there seven choices of thinking tools and yet only three stakes out. This research is important because it will explore if their choices are due to their characteristic of learning style and environment that need mind map than others. The other reason is that these thinking tools are easier to consume and use. Next factor could be that these thinking tools are the best for them in learning activities. Keywords: Thinking Tools, Manufacturing Students